STUDI THE HIDDEN CURRICULUM DALAM MEMBANGUN KARAKTER SISWA DAN MENINGKATKAN KECERDASAN SPIRITUAL DI MI TARBIYATUS SHIBYAN - Dedi Eko Riyadi (Program Studi Manajemen Pendidikan Islam IAIN Bone, 2023)
The approach used in this research is a psychological and sociological approach. The type of research is field research, which is a type of research based on data obtained directly from research sites in the field and is descriptive analytic in nature.In this study the authors raise important points of discussion in the area of how schools are trying through the application of a hidden curriculum to build student character and improve spiritual intelligence at MI Tarbiyatus ShibyanQualitative descriptive is a method used by researchers in order to carry out in-depth data analysis.The concept of implementing a hidden curriculum is to include character values that are included in all subjects. The character values that are instilled are religious values, independent values, values of appreciating achievement, values of curiosity, values of love for the motherland and creative values.Characterizations in elementary schools can encourage the development of students' spiritual intelligence by emphasizing religious values and discipline. The main concept of character education is based on the school's vision, mission and goals, which are related to curriculum and academic subjects, school culture both in the teacher's environment and in the student's environment as well as self-management through identification and development programs. student interests and talents. The concept of teaching character statistics is implemented through a hidden curriculum, including character statistics in all subjects. The character values contained are religious values, independent values, achievement appreciation values, curiosity values, patriotism values, and constructive values.